Compression stockings as an effective treatment for erythema nodosum: Case series - K.B. Golisch, BS; S.P. Gottesman, MD; R.J. Segal, MD (Wolters Kluwer, 2017)
Erythema nodosum (EN) is a septal panniculitis that is characterized clinically by tender, erythematous, subcutaneous nodules that are predominately localized on the pretibial lower legs. EN affects women more than men and can be idiopathic or secondary to another disease process such as infection or an immune response. Treatment options for erythema nodosum are suboptimal and often involve significant side effects or require a change in lifestyle. We investigated the effects of moderate 20 mmHg to 30 mmHg compression stockings as an alternative treatment method in two female patients with recurrent erythema nodosum. In both cases, the patients wore the compression stockings daily. At the follow-up visit, the EN lesions were no longer tender to the touch, and postinflammatory hyperpigmentation changes had started. Both patients had a lasting clinical resolution. Keywords: erythema nodosum, inflammatory conditions, quality of life, compression stockings, panniculitis